Distribution of Skeletal Metastases in Common Malignant Tumors: Observational Study at INMAS, Mohakhali - Sharmin, Rahima Akter; Quddus, Sharmin; Zohra, Fatema Tuz; Akter, Tania; Tasnim, Humayra; Hossain, Arshad; Alam, Md Jahir; Hossain, Mohammad Iqbal; Yasmeen, Nilufa; Zaman, Mahbuba (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Bone scan is a sensitive method for detecting bone metastases but not very specific. This means it can identify most cases of bone metastases but may also show false positives due to other conditions like arthritis or healing fractures (1). However, combining clinical data with bone scan results helps doctors narrow down the possible causes. The study aims to investigate how common cancers spread to bones using 99m Technetium-Methyl Diphosphonate ( 99m Tc-MDP). Study design: Single-center-based retrospective study Patients and Methods: 181 consecutive patients with malignancy (prostate cancer: 39, breast cancer: 108, lung cancer: 25, gastrointestinal cancers: 03, and others: 06) underwent bone scans. Results: Total 111 (61.32%) out of 181 patients had abnormal bone scans attributable to metastatic tumors. Bone metastases were found in 58.3%, 30.7%, 66.6%, 64%, and 80% of patients with breast, prostate, GI, and lung cancers and others, respectively. The most frequently involved area was the spine, followed by the ribs and pelvic bones. The spine was the most frequent site of bone metastases in breast and lung cancers. Except for the spine, common locations of bone metastases from breast cancer were ribs and sternum. In prostate cancer, the most frequent sites were the spine and pelvis, with similar incidences. In lung cancer, ribs, followed by the spine, were the most frequent sites of bone metastases. 91 (50.2%) of the cancer patients studied had symptoms of bone pain. The highest incidence was associated with metastatic lesions in bone scans. Significant correlation between the location of bone pain and evidence of bone metastasis in the same region was noticed in the pelvis, skull, sternum, spine, and femur. Conclusion: The spine, pelvis, breast, lung, and sternum are most frequently invaded in prostate, breast, and lung cancers, with bone pain in these areas being more significant for metastatic bone involvement. Bangladesh J. Nuclear Med. 28(1): 125-129, 2025